Wellspring of liberty how Virginia's religious dissenters helped win the American Revolution and secured religious liberty - Ragosta, John A. (Oxford University Press, 2010)
Virginia's dissenters, primarily Presbyterians and Baptists demanded religious liberty in return for supporting the American Revolution. The resulting negotiations not only brought Virginia, and America, religious freedom, but politicized dissenters and republicanized the polity.